Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I can't seem to find anything on the topic.

share|cite|improve this question
yes, itself !!!! – Anubhav Mar 19 at 13:08
Think it out. Let $g = e^{-1}$. Then $g*e = e^{-1}*e = e$. But $g*e = g$. So $g = e$. End of story. – fleablood Mar 19 at 16:41
... well, not quite end of story. Let $g = e^{-1}$. Then $g*h = e*(g*h) = (e*g)*h = e*h = h = h*e = h*(g*e) = (h*g)*e = h*g$. So for all $h$, $g*h = h* g = h$ so $g$ (whatever it is) is an identity element. No group has two identity elements; because then $g*e = e$ and $g*e = g$ which is a contradiction. So $g = e$. – fleablood Mar 19 at 16:47

All elements of a group have an inverse. This is a requirement in the definition of a group.

For an element $g$ in a group $G$, an inverse of $g$ is an element $b$ such that $gb = e$ where $e$ is the identity in the group. (Since the inverse of an element is unique, we usually denoted the inverse of $g$ $g^{-1}$ or $-g$.)

Note now that $ee =e$, so by definition $e$ is an inverse of itself.

You might be wondering if other elements might be their own inverses. The answer to this is yes. For example in the group $\mathbb{Z}_2$ of order $2$, both elements are their own inverse.

share|cite|improve this answer
In addition, all elements in $\mathbb{Z}_2 \times \mathbb{Z}_2 \times ... \mathbb{Z}_2$ are their own inverse, and thus there is no bound on the size of such groups. – Nate 8 Mar 20 at 3:46

Let $1$ be the identity element. Then its inverse $a$ is defined by $$ 1\cdot a = 1 $$ But $1 \cdot x = x$ so in particular $1 \cdot a = a$. Therefore, $a = 1$ and $1$ is its own inverse.

share|cite|improve this answer

If $e$ is the neutral element of $G$ then $eg=ge=g$ for all $g\in G$, in particular for $g=e$ then $ee=e$, ie $e=e^{-1}$.

share|cite|improve this answer

Let $g = e^{-1}$.

Then $g*e = e*g = e$. Solve for $g$.

Then $g*e = e \implies g*e*e^{-1} = e*e^{-1} => g = e$.

This gets kind of silly the more you think about it.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.